Localization of Topically Applied TFPI Binding Sites in an Intimectomized Microvessel - Ornberg, Richard L; Deune, Gene E; Ozbek, Mustafa R; Wun, Tze-Chien; Khouri, Roger K (Thrombosis and Haemostasis, 1995)
Tissue factor pathway inhibitor, TFPI, has been shown to be highly effective as a topically applied antithrombotic in an arterial model of vascular thrombosis. To elucidate the mechanism and site of TFPI action, recombinant TFPI was conjugated to 30 nm diameter gold particles and used to localize the sites of TFPI binding in a traumatized microvessel by transmission electron microscopy. The model, the central artery of the rabbit ear, was transected, denuded of endothelial lining (intimectomized), and re-anastomosed. Prior to the restoration of blood flow, TFPI-gold or unconjugated gold particles in solution were applied by irrigation to the intimectomized vessel lumen. After 10 min of blood flow, the artery was harvested for electron microscopy. TFPI-gold binding was localized to the fine strands of fibrin that lined the lumen of the intimectomized section of the artery. Little or no binding was found on platelets, exposed smooth muscle, cell membrane fragments, or uninjured vessel segments. The TFPI-gold binding could be competed with native TFPI. TFPI-gold was inhibitory, although less potent than native TFPI, in a prothrombin time assay. Unconjugated gold exhibited very little binding in the vascular model. Hence, the TFPI-gold conjugate behaved like native TFPI. Our observations have identified the fibrin complex as an in vivo binding site for TFPI and suggest that this is an in vivo site of action for TFPI as a topical antithrombotic agent.